The Effects of Peyton’S Four-Step Model on Students’ Learning Retention of Brick/Blocklaying and Concreting in Technical Colleges in Northeast, Nigeria - Usman, Akeem (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Brick/Blocklaying and Concreting (BBC) is a course offered in Technical Colleges in Nigeria that involve the exhibition of practical skill acquired by a learner. This study examined The Effects of Peyton’s Four-Step Model on Students’ Learning Retention of Brick/Blocklaying and Concreting in Technical Colleges in Northeast, Nigeria.The research employed quasi experimental research design with pre-test, post-test non-equivalent group design. The population for the study comprised 319 respondents National Technical Certificate (NTC) II students of BBC, from 19 Technical Colleges. Six technical colleges were selected in the zone using purposeful sampling technique; the sample size for the study was 103 NTC students. Instruments for data collection were Brick/Blocklaying and Concreting Cognitive Achievement Test (BBCCAT), and Brick/Blocklaying and Concreting Psychomotor Achievement Test (BBCPAT). The instruments were validated by experts. The data collected was analyzed in line with the research questions and hypotheses. The mean gain was used to answer research questions, while Analysis of covariance (ANCOVA) was used to test the null hypotheses at 0.05 level of significance, with the use of Statistical Package for Social Sciences (SPSS). The study found out that Peyton’s Four-step model: demonstration, reconstruction, comprehension and performance were significantly more effective in improving students’ retention in Brick/Blocklaying and Concreting than conventional method. The researcher recommends that: Peytons’ Four-step model should be incorporated into the content and methodology course of NTC programme of Brick/Blocklaying and Concreting, and should be extended to other vocational areas after its effect have been determine in those areas.